ANGELS: SISTEM PENILAIAN TINGKAT KESEHATAN (TKS) BANK SYARI’AH - Iwan Triyuwono (Universitas Brawijaya, 2011)
ANGELS: Bank Sharia System of Health Valuation Level. This article aims to formulate system of health valuation level for sharia banks. The formulation begins from philosophical foundation to a concrete form but not at practical level. The analysis starts by criticizing the utilitarianism ethics basic values that are contained in the conventional sharia bank valuation system (CAMELS), through sharia ethics basic values. The philosophical purpose of sharia banks is formulated structurally: process, results and stakeholders. Next, the valuation system concept is formulated in the form of ANGELS: Amanah management, Non-economic wealth, Give out, Earnings, capital and assets, Liquidity and sensitivity to market, as well as Socio-economic wealth. ANGELS: Sistem Penilaian Tingkat Kesehatan (TKS) Bank Syariah. Artikel ini bertujuan memformulasikan sistem penilaian tingkat kesehatan bank syari’ah. Konsep diformulasikan dari pemikiran filosofis hingga pada pemikiran yang lebih konkrit, namun tidak sampai pada tataran teknis. Analisis dimulai dari kritik terhadap dasar nilai etika utilitarianisme yang terkandung dalam konsep sistem penilaian tingkat kesehatan bank konvensional (CAMELS), melalui dasar nilai etika syari’ah. Berdasarkan pada nilai etika syari’ah ini, tujuan filosofis bank syari’ah diformulasikan dengan struktur: proses, hasil, dan stakeholders. Selanjutnya, konsep sistem penilaian tingkat kesehatan bank syari’ah dirumuskan dalam bentuk ANGELS: Amanah management, Non-economic wealth, Give out, Earnings, capital and assets, Liquidity and sensitivity to market, dan Socio-economic wealth.